Corporate Governance and Tax Avoidance: Moderating Effects of Institutional Ownership in Indonesia’s Energy Sector - Septiana Ferdiansyah; Lies Zulfiati (Santoso Academy Network, 2026)
This study examines the effects of profitability, thin capitalization, and Corporate Social Responsibility (CSR) on tax avoidance, as well as the moderating role of institutional ownership in energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. The energy sector was selected due to its capital-intensive nature, environmental impact, and high regulatory scrutiny regarding tax transparency. This study also addresses inconsistent findings in previous research concerning the determinants of tax avoidance and the effectiveness of institutional ownership as a governance mechanism. Using a quantitative associative approach, the research employed secondary data obtained from annual financial reports. Purposive sampling was used to select 30 companies, resulting in 120 firm-year observations. Data were analyzed using panel regression and moderation analysis in EViews. The results show that profitability has a significant negative effect on tax avoidance, indicating that more profitable firms tend to demonstrate greater tax compliance. Thin capitalization has a significant positive effect on tax avoidance, suggesting that debt financing encourages tax-minimization strategies through interest expense utilization. CSR reduces tax avoidance, while institutional ownership significantly moderates the relationships between profitability, thin capitalization, CSR, and tax avoidance by enhancing oversight and limiting opportunistic managerial behavior.